Synaptic clustering during development and learning: the why, when, and how - Winnubst, Johan; Lohmann, Christian (Frontiers in Molecular Neuroscience, 2012)
In order to contribute to a functional network a neuron must make specific connections and integrate the synaptic inputs that it receives in a meaningful way. Previous modeling and experimental studies have predicted that this specificity could entail a subcellular organization whereby synapses that carry similar information are clustered together on local stretches of dendrite. Recent imaging studies have observed exactly this kind of synaptic clustering during development and learning in different neuronal circuits. Interestingly, this organization is found to be dependent on synaptic activity through a mechanism that most likely involves local plasticity mechanisms. Here we discuss these new insights and give an overview of the candidate plasticity mechanism that could be involved.